Genus Viburnum: Therapeutic Potentialities and Agro-Food-Pharma Applications. (17th July 2021) - Sharifi-Rad, Javad; Quispe, Cristina; Vergara, Cristian Valdés; Kitic, Dusanka; Kostic, Milica; Armstrong, Lorene; Shinwari, Zabta Khan; Khalil, Ali Talha; Brdar-Jokanović, Milka; Ljevnaić-Mašić, Branka; Varoni, Elena M.; Iriti, Marcello; et al.
Abstract : The genus Viburnum (Adoxaceae, Dipsacales) is of scientific interest due to the chemical components and diverse biological activities found across species of the genus, which includes more than 230 species of evergreen, semievergreen, or deciduous shrubs and small trees. Although frequently used as an ornament, the Viburnum species show biological properties with health-promoting effects. Fruits, flowers, and barks of certain species are used for pharmaceutical purposes or as cooking ingredients, hence containing biochemical compounds with health-promoting activity such are carotenoids, polyphenols, and flavonoids. However, its taxonomical determination is difficult, due to its wide distribution and frequent hybridizations; therefore, an objective classification would allow us to understand its biological activity based on its phytochemical components. More than sixty phytochemical compounds have been reported, where vibsanin-type diterpenes and their derivatives are the most prevalent. Leaves and twigs of V. dilatatum contain the largest number of phytochemicals among the genus. Through preclinical evidence, this study provides insight regarding antioxidant, antibacterial, anti-inflammatory, cytotoxic, and anticancer activities of genus Viburnum .